Applied asset and risk management : a guide to modern portfolio management and behavior-driven markets /: a guide to modern portfolio management and behavior-driven markets. ([2014]) - Schulmerich, Marcus; Leporcher, Yves-Michel; Eu, Ching-Hwa
No abstract available